2012
DOI: 10.1111/j.1464-0597.2012.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity Effects in Graduates' Résumé Content

Abstract: Highly educated ethnic minority entrants in Western countries need more time to find a job compared to their Western ethnic majority counterparts. The present study examined whether this differential job access is partly explained by the way ethnic minorities present themselves in their résumés. To this end, a comparison between 100 non‐Western ethnic minority graduate résumés and 100 native Western ethnic majority graduate résumés was made. Non‐Western ethnic minorities score significantly lower on reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
2
16
0
1
Order By: Relevance
“…To avert age discrimination in the first phase of the screening procedure, policy makers as well as researchers recommended AAP (see Edin and Lagerström, 2006 ; Furtmueller et al, 2010 ; Åslund and Skans, 2012 ). Furtmueller et al (2010 , p. 10), for instance, concluded that “since employers are prohibited to select employees based on gender, birth date, nationality and marital status, resume forms should not ask for this personal information.” Anonymous resume screening omits explicit demographic cues from resumes that are non-job-related, like date of birth, ethnic-sounding name, or gender ( Edin and Lagerström, 2006 ; Åslund and Skans, 2012 ; Krause et al, 2012 ; Hiemstra et al, 2013 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To avert age discrimination in the first phase of the screening procedure, policy makers as well as researchers recommended AAP (see Edin and Lagerström, 2006 ; Furtmueller et al, 2010 ; Åslund and Skans, 2012 ). Furtmueller et al (2010 , p. 10), for instance, concluded that “since employers are prohibited to select employees based on gender, birth date, nationality and marital status, resume forms should not ask for this personal information.” Anonymous resume screening omits explicit demographic cues from resumes that are non-job-related, like date of birth, ethnic-sounding name, or gender ( Edin and Lagerström, 2006 ; Åslund and Skans, 2012 ; Krause et al, 2012 ; Hiemstra et al, 2013 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a Dutch study, Hiemstra et al (2013) showed that in the absence of demographic information (as in anonymous resume screening), real recruiters still gave lower job suitability ratings to resumes of ethnic minority applicants compared to those of their majority counterparts. Whereas human capital factors could explain these findings to some extent, Hiemstra et al (2013) could not exclude hiring discrimination, either.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a similar way, Kuh et al (2006) state that ethnic minority students may be more likely to take additional jobs for financial reasons. Due to this stronger financial necessity, ethnic minority students seem to work longer hours and report less relevant work-related experiences, such as work-related supervisory positions and achievement (Hiemstra et al 2013;Warren et al 2000). Aside from these studies on average differences and experiences, as far as we know, up until now no prior research has been done into possible differences in the work-study interface related to ethnicity.…”
Section: Antecedents Of the Work-study Interfacementioning
confidence: 99%
“…A second area where there are clear disparities is in terms of ethnicity. Studies that have used correspondence audit techniques have shown marked differences in obtaining interviews for those from different ethnic origins, even when the details on the resumés were standardized Derous, Ryan, & Nguyen, 2012;Hiemstra, Derous, Serlie, & Born, 2013). Although gender was found to moderate the ethnicity effect, there were clearly lower success rates for this group of candidates.…”
Section: Different Trajectories To the Same Destination?mentioning
confidence: 94%